Efektivitas Metode Zero One Dalam Manajemen Resiko Pekerjaan Konstruksi Gedung Berlantai (Studi Kasus Gedung Kuliah Fakultas Kehutanan Dan Ilmu Lingkungan Universitas Halu Oleo Kendari) - Soeparyanto, Try Sugiyarto; Nirah, Jalba; Nuhun, Ridwan Syah; Fadil, La Ode muhammad; Prasetya, Dhalmaz; Putra P, Dwi Bayu; Ali, Muhammad Alfian (Universitas Sulawesi Tenggara, 2024)
This study aims to analyze the visibility of the Zero-One method in the construction of the Faculty of Forestry and Environmental Sciences Building, Halu Oleo Kendari University, Southeast Sulawesi. The results of the analysis showed that a weak control system was the main cause of delays and additional costs in this project. This variable has the highest weight, reaching an average of 90.38, in line with secondary data in the form of monthly reports from the project which show that there is a delay of 1-2 weeks of working days in the process of vertical formwork on floor plate work 2-3, this has a major impact on project time and cost. Corrective measures that can be suggested include optimization of staff performance through material training and risk management, as well as better strategies to address weak systems and avoid delays. The results of this analysis also highlight other risks such as errors in budget planning, material expenditure, and inefficient use of materials. This research was conducted by collecting data from 9 respondents involved in the project. In parallel with the secondary findings of the monthly report of the project, it was identified that there were delays in certain construction processes. Addressing efforts include increasing working hours and manpower to catch up with delays and minimize the addition of inefficient costs. The study provides valuable insights for improving risk management and efficiency in construction projects, focusing on cost and time control systems.